Pengaruh Implementasi Model Pembelajaran PBL (Problem Based Learning) terhadap Hasil Belajar Matematika dan Keterampilan Berpikir Kritis: The Effect of Problem-Based Learning (PBL) Model Implementation on Mathematics Learning Outcomes and Critical Thinking Skills - Kurnia, Dicky (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
This study aims to investigate the effect of implementing the Problem-Based Learning (PBL) model on the mathematics learning outcomes and critical thinking skills of junior high school students. The research was conducted using a quasi-experimental method with a pretest-posttest control group design. The sample consisted of 64 eighth-grade students from a public junior high school in Cianjur, divided into an experimental class (n=32) that received instruction with the PBL model and a control class (n=32) that received conventional instruction. The instruments used were a validated mathematics learning outcomes test on the topic of probability and a validated critical thinking skills test. Data were analyzed using an independent samples t-test and correlation analysis. The results showed that: (1) there was a significant difference in mathematics learning outcomes between students who followed the PBL model compared to the conventional model (p